Transfer of functional microorganism: Regulation of N-acyl-homoserine lactones on the microbial community in aniline-degrading sequencing batch biofilm reactor. (May 2022) - Su, Junhao; Zhang, Qian; Huang, Wansong; Song, Jianyang; Peng, Haojin; Feng, Jiapeng; He, Jing; Zhang, Yunjie; Wei, Hua
Graphical abstract: Highlights: Nitrogen removal of aniline-degrading SBBR was improved by exogenous AHLs. Nitrifiers and denitrifiers were enriched in biofilm. The relationships of nitrogen removal genera were promoted obviously. The main nitrogen removal contributors shifted from sludge to biofilm. Abstract: Due to the inhibition of nitrification from aniline toxicity, exogenous N-acyl-homoserine lactones (AHLs) addition was attempted to enhance nitrogen removal in this work. Two sequencing batch biofilm reactors (SBBRs): S1 (the control) and S2 (C6-HSL and 3-oxo-C8-HSL dosing) were used to treat aniline wastewater. The NH4 + -N and TN removal rates of S2 were 42.50% and 26.99% higher than S1 in the aerobic phase, respectively. It revealed the nitrogen removal performance of S2 much better than S1. High-throughput sequencing results indicated that many nitrifiers and denitrifiers of S2, such as Nitrosomonas and Thauera, transferred from sludge to biofilm significantly and built closer relationships each other. Overall, main nitrogen removal was contributed by biofilm rather than sludge with the regulation of AHLs. A mild and collaborative environment of biofilms for microorganisms enhanced nitrogen removal. The work provided a new idea for reconciling the contradiction between nitrification and denitrification in aniline wastewater treatment.